2017
DOI: 10.1149/2.0411706jes
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Na2SO4Deposit Induced Corrosion of Cr, Al, C Binary and Ternary Thin Film Coatings on Ni-201

Abstract: Al-C, Cr-C, Al-Cr and Al-Cr-C thin film coatings were sputtered onto Ni-201 substrates. Samples were deposited with 1.0 ± 0.3 mg cm −2 Na 2 SO 4 and exposed to dry air/2 ppm SO 2 gas atmosphere, at 700 • C for 250 hours. Coated samples had reduced corrosion rates relative to uncoated samples. Al-C and Cr-C coatings were not effective since NiO was the only compound detected on the surfaces; in contrast Cr-Al and Cr-Al-C developed protective layers of Al 2 O 3 and Cr 2 O 3 with Cr-Al-C coated samples having the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Although testing at 700°C, under a p(SO2) of 2 ppm for 250 h, diffused the coating into the Ni surface layer, it was more resistant to oxidation under Na2SO4 salt deposits than Al-C, Cr-C, Al-Cr binary films or the bare substrate. [10] A diffusion bonded hybrid Cr2AlCsuperalloy couple was found to be mechanically and environmentally stable after multiple cycles and thermal exposure to 800°C for 1000 h. While little additional interdiffusion occurred at 800°C, bonding at 1100°C for 2 h had already produced appreciable 50 µm layers of NiAl and Cr7C3. [11] Finally, a 760°C low cycle fatigue study demonstrated no additional detriment of hot corrosion to LCF life for a Cr2AlC-coated LSHR (low solvus, high refractory) disk superalloy.…”
Section: ) Introductionmentioning
confidence: 96%
“…Although testing at 700°C, under a p(SO2) of 2 ppm for 250 h, diffused the coating into the Ni surface layer, it was more resistant to oxidation under Na2SO4 salt deposits than Al-C, Cr-C, Al-Cr binary films or the bare substrate. [10] A diffusion bonded hybrid Cr2AlCsuperalloy couple was found to be mechanically and environmentally stable after multiple cycles and thermal exposure to 800°C for 1000 h. While little additional interdiffusion occurred at 800°C, bonding at 1100°C for 2 h had already produced appreciable 50 µm layers of NiAl and Cr7C3. [11] Finally, a 760°C low cycle fatigue study demonstrated no additional detriment of hot corrosion to LCF life for a Cr2AlC-coated LSHR (low solvus, high refractory) disk superalloy.…”
Section: ) Introductionmentioning
confidence: 96%
“…Cr 2 AlC also has excellent resistance to Type I molten salt (Na 2 SO 4 ) hot corrosion at 900-1000°C [141,142] and shows promising Type II low-temperature hot corrosion behaviour [152,245]. Molten ash can penetrate the YSZ hot surface and cause fracturing or delamination upon cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [90,99] demonstrated that bulk Cr 2 AlC exhibits excellent resistance to Type I molten salt (Na 2-SO 4 ) hot corrosion at 900-1000°C, which can be attributed to the formation of a protective Al 2 O 3 -rich scale during the hot corrosion processes. Furthermore, Aw et al [273] reported improved Type II low-temperature hot corrosion behaviour of the Ni-superalloy coated with sputtered Cr-Al-C films relative to uncoated samples.…”
Section: Hot Corrosion Resistance Of Max Phasementioning
confidence: 99%